2012
DOI: 10.1515/epoly.2012.12.1.160
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of pectin, poly(vinyl alcohol) and their blends in aqueous solutions

Abstract: The new blends composed of natural polysaccharide -pectin and synthetic water soluble polymer -poly(vinyl alcohol) (PVA) are attractive materials due to their biocompatibility, non-toxicity and biodegradability. In this work the rheological properties of aqueous solutions of pectin (PEC), poly(vinyl alcohol) and their mixtures at various weight ratios (70/30, 50/50, 30/70) have been investigated. Flow measurements were carried out using a rotary viscometer with concentric cylinder at different temperatures (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
(27 reference statements)
2
10
1
Order By: Relevance
“…It is in accordance with previously reported data for the solutions of PAM [19,20]. The decrease of apparent shear viscosity with the shear rate is mainly related to the orientation of macromolecules along the streamline of flow and to the disentanglement of macromolecules with the increasing shear force [19][20][21][22]. However aqueous solutions of mixtures at w MCCh ≤ 0.5 exhibit the higher apparent viscosity than the apparent viscosity of native polymers.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…It is in accordance with previously reported data for the solutions of PAM [19,20]. The decrease of apparent shear viscosity with the shear rate is mainly related to the orientation of macromolecules along the streamline of flow and to the disentanglement of macromolecules with the increasing shear force [19][20][21][22]. However aqueous solutions of mixtures at w MCCh ≤ 0.5 exhibit the higher apparent viscosity than the apparent viscosity of native polymers.…”
Section: Resultssupporting
confidence: 91%
“…For the solutions of MCCh I and MCCh I/PAM mixtures, the shear-thickening behavior is observed. The shear-thickening behavior may be related to the change of macromolecular conformation induced by flow [19][20][21][22]. In the case of the mixture solutions, the intermolecular interaction participates in the shear thickening phenomenon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…0.2 Pa•s) [57] and viscosity obtained for 5% pectin solutions of cacao pod husks [58] and apple pomace [59], which was lower than 0.2 Pa•s. Figure 4 presents the flow curves of the three pectin samples; all curves present a shear thinning behaviour of a non-Newtonian fluid due to the weakness of the pectin intermolecular forces with increasing shear rate [55,56]. It can be observed that the origin of pectin had no influence on the thinning behaviour of the solutions, as all of them had the same behaviour, showing viscosity decrease with the increasing of shear rate.…”
Section: Thermal Analysismentioning
confidence: 95%